Some Compositional Approaches in the Practice of live-electronic music from the perspective of technique and technological tools - de Oliveira, Vinícius Cesar; Pessanha, Thales Roel P. (Revista Vórtex, 2021)
Tools and their technical frameworks impact directly the compositional processes, thus, placing itself as an element of fundamental importance, either in the conception of poetic ideas and images or in the technical realization of a work. In this sense, the present work aims to discuss some aspects of the correlation between technics, poetics, aesthetics, and musical writing in the context of interactive/live-electronics music. This takes place from a dialogue between the ideas of authors and composers, such as Gilbert Simondon, Helmut Lachenmann, and Pierre Boulez about technical frameworks and their implications in musical practice. Thus, we aim to discuss the interrelation between technological devices, musical elements, and poetic images, which are established within the compositional process. These reflections will serve as a theoretical field to introduce and describe some characteristics about compositional thinking of two-piece: "Espasmos" (2017), for trombone and live-electronics, by Vinicius Cesar, and "Caminhos que Levam" (2018), for clarinet and live-electronics, by Thales Roel.